Two Novel NF1 Pathogenic Variants Causing the Creation of a New Splice Site in Patients With Neurofibromatosis Type I - Setrajcic Dragos, Vita; Blatnik, Ana; Klancar, Gasper; Stegel, Vida; Krajc, Mateja; Blatnik, Olga; Novakovic, Srdjan (Frontiers in Genetics, 2019)
Neurofibromatosis type I (NF1) is one of the most common autosomal dominant disorders, since the estimated incidence is one in 3,500 births. In this study we present bioinformatical and functional characterization of two novel splicing NF1 variants, detected in NF1 patients. Patient 1, carring NF1:c.122A>T, which introduces a new exonic 5' donor splice site, was diagnosed with hormone positive, Her-2 negative breast cancer at the age of 47. She had an atypical presentation of NF1, with few café-au-lait spots and no Lisch nodules. ShePatient developed a hemothorax due to subclavian artery rupture, which has previously been described as an extremely rare complication of NF1. Patient 2, carring NF1:c.7395-17T>G that creates a new intronic 3' acceptor splice site, had quite a typical clinical presentation of NF1: formations on her tongue in the region of her left metacarpal bones and on her left foot, plexiform neurofibroma in her pelvis, several café-au-lait spots and axillary freckling. She was also diagnosed with cognitive impairment. In the report we are presenting two novel variants which were successfully classified based on NGS and mRNA analysis. Based on results of mRNA analysis both variants were classified as likely pathogenic according to ACMG guidelines applying evidence categories PS3, PM2, PP3, PP1-supporting. By characterizing those two novel NF1 splicing variants, we have confirmed the neurofibromatosis type I phenotype in the two probands.